2008
DOI: 10.1128/mmbr.00008-08
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Functions of Mycothiol, the Unique Protective Thiol of Actinobacteria

Abstract: SUMMARY Mycothiol (MSH; AcCys-GlcN-Ins) is the major thiol found in Actinobacteria and has many of the functions of glutathione, which is the dominant thiol in other bacteria and eukaryotes but is absent in Actinobacteria. MSH functions as a protected reserve of cysteine and in the detoxification of alkylating agents, reactive oxygen and nitrogen species, and antibiotics. MSH also acts as a thiol buffer which is important in maintaining the highly reducing environment within the cell and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
293
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(303 citation statements)
references
References 160 publications
(250 reference statements)
2
293
0
2
Order By: Relevance
“…Instead, these organisms use the small molecule mycothiol (MSH) 2 as their primary reducing agent and in xenobiotic metabolism for the detoxification of drugs and other toxins (1)(2)(3)(4). MSH is likely to be critical for the survival of mycobacteria inside activated macrophages, where the mycobacteria are subjected to oxidative bursts.…”
mentioning
confidence: 99%
“…Instead, these organisms use the small molecule mycothiol (MSH) 2 as their primary reducing agent and in xenobiotic metabolism for the detoxification of drugs and other toxins (1)(2)(3)(4). MSH is likely to be critical for the survival of mycobacteria inside activated macrophages, where the mycobacteria are subjected to oxidative bursts.…”
mentioning
confidence: 99%
“…Also, enhanced resistance to ETH is another characteristic of the MshA-, MshB-, and MshDdeficient mutants, with complete resistance at 50 μg/mL [52,53]. The high levels of resistance of the MSH mutants to 3 and ETH suggest that MSH is involved in the activation of these drugs, because both 3 and ETH are prodrugs which need to be activated intracellularly and whose reactive groups must be unmasked before inhibiting their target [54]. Recently, it was demonstrated that mutations in MSH biosynthesis genes may contribute to INH or ETH resistance across mycobacterial species, because these mutants showed low-level resistance to INH but were highly resistant to ETH [55].…”
Section: Eth Metabolismmentioning
confidence: 99%
“…Also, enhanced resistance to ETH is another characteristic of the MshA-, MshB-, and MshDdeficient mutants, with complete resistance at 50 μg/mL [52,53]. The high levels of resistance of the MSH mutants to 3 and ETH suggest that MSH is involved in the activation of these drugs, because both 3 and ETH are prodrugs which need to be activated intracellularly and whose reactive groups must be unmasked before inhibiting their target [54]. Recently, it was demonstrated that mutations in MSH biosynthesis genes may contribute to INH or ETH resistance across mycobacterial species, because these mutants showed low-level resistance to INH but were highly resistant to ETH [55].…”
Section: Eth Metabolismmentioning
confidence: 99%